RANCANG BANGUN SISTEM MONITORING DAN CONTROLLING SUHU COOL BOX VAKSIN MENINGITIS MPSV4 BERBASIS IoT - Anisa Khoirul Umami; Dendy Kurniawan (Pusat Riset dan Inovasi Nasional, 2023)
Meningitis is generally an infectious disease of the lining of the brain and spinal cord with manifestations of fever and stiff neck. Prevention efforts for meningitis include vaccination. Meningococcal polysaccharide vaccine (MPSV4) is a type of quadrivalent meningitis vaccine recommended to control meningitis outbreaks. In storage, this vaccine uses a cold chain and cool box with a temperature between 2-8˚C. For vaccination activities, the vaccine is stored in a cool box with a cool pack provided to maintain temperature stability in the cool box. A cool pack itself is a rectangular plastic container that is filled with water and then cooled in a refrigerator at a temperature of 2-8°C for a minimum of 24 hours. From the existing problems, the author had the idea to create an IoT-based MPSV4 Meningitis Vaccine Cool Box Temperature Monitoring and Controlling System Design. The working system of this tool, namely TEC, will maintain the cool box temperature according to needs. If the dht11 detects that the temperature is too high then both TECs will turn on, whereas if the temperature is stable then one of the TECs will turn off. The temperature inside the cool box will be displayed on the LCD and also sent via the NodeMCU ESP8266 to the Firebase database which will then be displayed on the smartphone in real time.